2014
DOI: 10.1104/pp.114.243931
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Fruit Chromoplasts Behave as Respiratory Bioenergetic Organelles during Ripening

Abstract: During tomato (Solanum lycopersicum) fruit ripening, chloroplasts differentiate into photosynthetically inactive chromoplasts. It was recently reported that tomato chromoplasts can synthesize ATP through a respiratory process called chromorespiration. Here we show that chromoplast oxygen consumption is stimulated by the electron donors NADH and NADPH and is sensitive to octyl gallate (Ogal), a plastidial terminal oxidase inhibitor. The ATP synthesis rate of isolated chromoplasts was dependent on the supply of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 57 publications
0
50
0
Order By: Relevance
“…In chromoplasts isolated from tomato ( Solanum lycopersicum cv. Micro‐Tom; Renato et al ), generation of a proton motif force by electron transport involving the NDH complex, PQ and PTOX has been shown to take place. The same is the case in etioplasts (Kambakam et al ).…”
Section: Alternative Electron Transport Pathways In Gerontoplastsmentioning
confidence: 99%
“…In chromoplasts isolated from tomato ( Solanum lycopersicum cv. Micro‐Tom; Renato et al ), generation of a proton motif force by electron transport involving the NDH complex, PQ and PTOX has been shown to take place. The same is the case in etioplasts (Kambakam et al ).…”
Section: Alternative Electron Transport Pathways In Gerontoplastsmentioning
confidence: 99%
“…Tomato chromoplasts were recently observed to synthesize ATP through chromorespiration activites of respiratory bioenergetic organelles during fruit ripening (Pateraki et al, 2013;Renato et al, 2014). Wang et al (2013) also observed high metabolic activities and an abundance of transport-related proteins in watermelon chromoplasts.…”
Section: Discussionmentioning
confidence: 98%
“…Chromoplasts from different species use either NADPH or NADH as the preferred electron donor. Addition of NADH resulted in higher respiratory activity in tomato chromoplasts than NADPH (Renato et al ., ), while the opposite was found with daffodil chromoplasts (Nievelstein et al ., ). Chromorespiration may be related to a similar process in chloroplasts, chlororespiration, first been described by Bennoun () as a light‐independent electron transport pathway from NAD(P)H to O 2 .…”
Section: Introductionmentioning
confidence: 92%
“…The tomato chromoplast proteome revealed the presence of NDH complex subunits and of the cytochrome b 6 f complex (Barsan et al ., ; Wang et al ., ), rendering these two likely components of the respiratory electron transport chain. Furthermore, it has been suggested that a type II NDH contributes to the reduction in the PQ pool (Renato et al ., ). The participation of the cyt b 6 f complex in chromorespiration is corroborated by the partial sensitivity of ATP synthesis to DBMIB, an inhibitor of the cyt b 6 f complex (Renato et al ., ).…”
Section: Introductionmentioning
confidence: 97%